HIV/AIDS KNOWLEDGE AND RISK PERCEPTION OF VISUALLY IMPAIRED AND SIGHTED PUPILS IN KENYA - Lydia, Kendi; Maureen, Mweru; Theresia, Kinai (European Scientific Journal, ESJ, 2012)
The aim of this study was to find out HIV/AIDS knowledge level, and perception of risk of infection with HIV/AIDS, of visually impaired and sighted pupils. Differences between visually impaired and sighted pupils HIV/AIDS knowledge and perception of risk of infection were studied. Descriptive survey was used to collect data. The sample included 116 pupils. The mean score for HIV/AIDS knowledge was 92.94% and 87.59% for sighted pupils and visually impaired pupils respectively. The risk perceptions mean score for sighted and visually impaired pupils was 71.08% and 68.03% respectively. There were significant statistical differences between sighted and visually impaired pupils’ knowledge of HIV/AIDS and perception of risk of infection with HIV/AIDS. This study recommended the government and other stakeholders increase education programmes to address misconceptions about transmission and make available HIV/AIDS information in accessible formats for the visually impaired through Braille, audio tapes and large print visual aids.